Encyclopedia of Distance Learning, Second Edition 2009
DOI: 10.4018/978-1-60566-198-8.ch166
|View full text |Cite
|
Sign up to set email alerts
|

Informal Communication in Virtual Learning Environments

Abstract: Learning environments increasingly become more diverse by the use of information technology. Thereby, the share of face-to-face situations between students as well as between students and mentors becomes smaller, while the share of encounters in virtual space is growing larger. Thus, computer mediated communication (CMC) is growing in importance in all learning environments. Since standard learning environments involve both formal and informal communication, it seems reasonable to claim that without informal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For the QM data by Hättig et al, some discrepancies can be observed in the lowtemperature region since quantum effects become stronger with decreasing temperatures. In the paper of Gaiser and Fellmuth [39], they also reported one b value at 273.16 K computed by Bich [42], where b = B ε /A ε . Using the information provided by Gaiser and Fellmuth, we have determined the B ε data of Bich and its uncertainty (See the supplementary materials for more detials).…”
Section: Comparisons With the Computed Values In The Literaturementioning
confidence: 97%
See 4 more Smart Citations
“…For the QM data by Hättig et al, some discrepancies can be observed in the lowtemperature region since quantum effects become stronger with decreasing temperatures. In the paper of Gaiser and Fellmuth [39], they also reported one b value at 273.16 K computed by Bich [42], where b = B ε /A ε . Using the information provided by Gaiser and Fellmuth, we have determined the B ε data of Bich and its uncertainty (See the supplementary materials for more detials).…”
Section: Comparisons With the Computed Values In The Literaturementioning
confidence: 97%
“…To facilitate the applications in temperature and pressure metrology, the second dielectric virial coefficient of helium4 between 5 and 25 K will be computed in this work by the method of analog. Moszynski and coworkers have calculated 1999 4 He, Ar SC 3.8-408 K Rizzo [41] 2002 4 He, Ar QM 3.8-408 K Hättig [19] 2003 Ne SC, QM 40-410 K Bich [42] 2009 Ne U 273 K Vogel [20] 2010 Ar SC 84-10 000 K Cencek [18] 2011 4 He C 77-322 K a C, classical; QM, quantummechanical; SC, semiclassical; U, unknown.…”
Section: Ne-nementioning
confidence: 99%
See 3 more Smart Citations